Factors influencing first-time voters' turnout in the 2024 legislative elections: Political efficacy, campaign strategies, and financial incentives - Mulyawan, Wawan; Rifai, Rifai; Hidayat, Rahmad (The International Journal of Politics and Sociology Research, 2024)
This article explores the complexity of factors that mobilize the participation of first-time voters in the 2024 Legislative Election in Rabadompu Timur Village, Raba District, Bima City, West Nusa Tenggara Province. The low level of involvement of first-time voters in the general election process in Indonesia is the imperative basis for exploring the root causes underlying this phenomenon in order to strengthen the integrity and inclusiveness of electoral democracy. The urgency of this study is based on tracing the path of first-time voter participation, which has a crucial function in strengthening the legitimacy of the general election results through identifying dominant determinants in the form of political efficacy levels, candidate campaign strategies, and financial incentives. Data were collected from interviews with 20 first-time voters. The results of the study show that political efficacy plays an important role in encouraging participation, where voters with high confidence in their ability to influence election results tend to be more active. Candidate campaign strategies that utilize social media effectively also increase the involvement of first-time voters, although overly aggressive campaigns can actually reduce participation. In addition, financial incentives have been shown to mobilize some voters, although many still consider the candidate's program. These findings provide practical insights for policymakers and candidates in increasing the political participation of first-time voters, as well as offer theoretical contributions to the literature on voter behaviour.